Sport Education Model: Improving Student Motivation in Physical Education - Hasyim; Ramdan, Gilang; Putra, Dede Dwiansyah; Putra, Dede Dwiansyah; Okilanda, Ardo; Mulayana, Nanang; Hadiana, Oman; Iskandar, Dedi; Iskandar, Dedi; Fajar, Mutiara (International Journal of Psychosocial Rehabilitation, 2020)
The research conducted aims to determine the increase in student motivation after finding the learning process by using a sports education model (SEM) with a traditional learning model. The method used is Nonequivalent Control Group Design which uses 50 students as research subjects which are divided into 2 groups. Based on the findings in this study revealed a sense of comfort in students during learning activities carried out by using the sports education model (SEM) this can be seen from the activities of the involvement of all students in each learning activity with a sense of comfort and pleasure in the learning that they participated in. The results of this study suggest that almost all students involved in the learning process using SEM enjoy the model because the learning presented is not only in the form of understanding of skills but more on personal and social skills. Conclusion Sports Education Model (SEM) is very effective to be used in sports learning because this model can actively involve all students, also SEM presents competition in the learning process so that this will cause very high motivation among students so that the learning process will be very competitive.